2023
DOI: 10.1021/acs.est.2c09140
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Order to Photoaging and Humic Acids Significantly Modifies the Aggregation and Transformation of Nanoplastics in Aqueous Solutions

Abstract: The colloidal stability of nanoplastics in aqueous solutions is greatly regulated by photoaging and dissolved organic matter (DOM). However, how the exposure order to sunlight and DOM modifies the environmental behavior of nanoplastics is seldomly determined. Here, with two different exposure orders, we investigated the impact of molecular-weight (MW)-fractionated humic acids (HAs) derived from biochar and the Suwannee River, respectively, on the aggregation of poly(ethylene terephthalate) nanoplastics (PET-NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The addition of Suwannee River humic acid (SRHA) under simulated seawater showed that the critical coagulation concentration (CCC) value of PET-NP was 98 mmol/L for Na + at pH = 5.8, and the CCC value of PET-NP decreased after the addition of different molecular weights of SRHA in NaCl solution, implying that the stability of NPs decreased and became vulnerable to aggregation. The smaller molecular weight HA resulted in the greatest decrease in the CCC of PET-NP, from 98 mmol/L to 53 mmol/L, while the larger molecular weight HA introduced a higher steric hindrance along with a decrease in the ζ potential of PET-NP, which partially counteracted the aggregation effect …”
Section: Reaction With Natural Colloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of Suwannee River humic acid (SRHA) under simulated seawater showed that the critical coagulation concentration (CCC) value of PET-NP was 98 mmol/L for Na + at pH = 5.8, and the CCC value of PET-NP decreased after the addition of different molecular weights of SRHA in NaCl solution, implying that the stability of NPs decreased and became vulnerable to aggregation. The smaller molecular weight HA resulted in the greatest decrease in the CCC of PET-NP, from 98 mmol/L to 53 mmol/L, while the larger molecular weight HA introduced a higher steric hindrance along with a decrease in the ζ potential of PET-NP, which partially counteracted the aggregation effect …”
Section: Reaction With Natural Colloidsmentioning
confidence: 99%
“…The smaller molecular weight HA resulted in the greatest decrease in the CCC of PET-NP, from 98 mmol/L to 53 mmol/L, while the larger molecular weight HA introduced a higher steric hindrance along with a decrease in the ζ potential of PET-NP, which partially counteracted the aggregation effect. 70 The formation of eco-corona also leads to changes in the ecotoxicity of NPs and their capacity to carry pollutants, which can alter the "Trojan horse effect" of NPs. 66 The "Trojan horse effect" refers to NPs acting as carriers for other pollutants and transporting them.…”
Section: Reaction With Natural Colloidsmentioning
confidence: 99%